2019
DOI: 10.1109/tpwrs.2019.2905433
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Consensus-Based Control of $\mu$Gs With Communication Delays and Noises

Abstract: We propose a novel stochastic consensus-based secondary voltage and frequency restoration scheme with communication delays and noises for islanded microgrids (µGs). Existing distributed methods commonly design restoration layer with the assumption of ideal communication among distributed generations (DGs). Albeit, the communication channels are exposed to delay and noise, whereas any DG receives delayed and noisy measurements from its neighbors due to peripheral noises and communication delays. Delay and noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…in which I and 0 are identity and zero matrices, K is the gain to be designed in (21), and ⊗ represents kronecker product. In the following, we claim that Ξ = lim t → ∞ E[π(t)π(t) T ] exists and is obtained from the following Lyapunov equation:…”
Section: Distributed Robust Stochastic Voltage Restoration Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…in which I and 0 are identity and zero matrices, K is the gain to be designed in (21), and ⊗ represents kronecker product. In the following, we claim that Ξ = lim t → ∞ E[π(t)π(t) T ] exists and is obtained from the following Lyapunov equation:…”
Section: Distributed Robust Stochastic Voltage Restoration Controlmentioning
confidence: 99%
“…Proof: See equations (3)- (21). □ The main feature of our proposed distributed protocol is that the designed protocols are based on the relative estimated state, under which the consensus error can be characterised using the Lyapunov equation's solution.…”
Section: Distributed Robust Stochastic Voltage Restoration Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Several research studies on "noise-resilient" control strategies of microgrids have been reported. 14,[50][51][52][53][54] Additive noise is statistically modeled with "Gaussian distribution". 14,[50][51][52][53][54] Without any loss of generality, we have modeled noise with a "zero-mean white Gaussian" model.…”
Section: Impact Of Communication Delay and Noise On System Performancementioning
confidence: 99%
“…14 White noise with a variance of 0.1 is considered for the simulation. 14,50 The time response with a communication delay (of 30 ms) and white noise ("zero-mean white Gaussian" with a variance of 0.1) is shown in Figure 15. We observe that the system performs satisfactorily even with additive noise.…”
Section: Impact Of Communication Delay and Noise On System Performancementioning
confidence: 99%